Heavy Metals Concentration in Sea Water at Cilegon Coastal Waters - Ishlahul Fikri; Ibrahim Ahmad; Afda Refani; Adhika Putra Agra Wijnana; Nur Jamiah Rangkuti; Ivana Rindi Antika P (Journal of Bioresources and Environmental Sciences, 2026)
Cilegon City is an industrial city with an area of 175.51 km2, approximately 43.6% of which is comprised of coastal and marine areas. Industrial activities, ports, and even household waste can produce pollutants that flow into the sea. One of the pollutants entering the waters is heavy metals. Common heavy metals found are Cadmium (Cd), Copper (Cu), and Lead (Pb). This research was conducted in February 2022 in the waters of Cilegon. Heavy metal concentration measurements were conducted at an ISO 17025:2017 accredited laboratory. One liter of seawater samples was from the surface (0-50 cm), filtered, and HNO3 preservative was added to a pH of 2 in polyethylene bottles. Measurements of aquatic environmental quality parameters, including temperature, salinity, and pH, were conducted in situ. Dissolved heavy metal concentrations were analyzed descriptively and compared with seawater quality standards in accordance with Government Regulation Number 22 of 2021 concerning the implementation of environmental protection and management. Water quality assessment was conducted by calculating the Pollution Index in accordance with the Decree of the Minister of Environment Number 115 of 2003. The results of the water temperature measurements ranged from 28.8 to 30.4°C, salinity ranged from 29 to 31 ppm, and the water pH obtained was 7.7 to 8.4, which stated that the environmental parameters of the waters met the quality standards. The concentration of dissolved Cd was <0.00003 at all stations. The concentration of dissolved Cu obtained ranged from <0.006 to 0.0129 mg/l; two stations obtained results exceeding the quality standards. The concentration of dissolved Pb obtained ranged from <0.00012 to 0.017 mg/l; two stations exceeded the quality standards. The results of the water pollution index calculations stated that all research stations were in a slightly polluted condition.